How has the landscape changed? Landscape transformation analysis of Ogrodzieniec-Podzamcze (POLAND) using landgraphy and landscape stratigraphy methods. - Urszula Myga-Piątek; Anna Żemła-Siesicka (Landscape Online, 2023)
This article presents a combination of landscape biography and stratigraphy as a method for the visualisation of historical landscape change. The main goal was to analyse the evolution of the cultural landscape of part of the Ogrodzieniec municipality – Podzamcze (Częstochowa Upland, Poland). The evolution of the landscape was reconstructed based on cartographic materials (topographic maps from the last 200 years) and scholarly literature. The results show the dominance of the agricultural landscape in all studied periods. The forest and settlement landscapes expanded significantly within the studied period. The fortified landscape is clearly visible as a core running through all the years. The results indicate changes of an evolutionary type and heterogenous (genetically), heterotonic (in terms of land cover) form. The method can be used in well-documented areas to visualise the past and contemporary landscapes and to forecast future ones, so it can be useful in landscape planning.